CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Expand : $$(4x-3y-2z)^{2}$$.


Solution

$$ (4x-3y-2z)^{2} = [(4x-3y) - (2z)]^{2}$$
$$ = (4x-3y)^{2}-2(4x-3y) -(2z)+4z^{2}$$
$$ = 16x^{2} = 2 \times 4x\times 3y+9y^{2} - 2 [ 8xz-6y^{2}] + 4z^{2}$$
$$ = 16x^{2} - 24xy + 9y^{2} - 16xz + 12yz + 4z^{2}$$

1229463_1299196_ans_9fd3611c62af43a092c80b1b51137833.jpg

Maths

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image